One-dimensional anodic TiO2 nanotubes coated by atomic layer deposition: Towards advanced applications - Dvorak, Filip; Zazpe, Raul; Krbal, Milos; Sopha, Hanna; Prikryl, Jan; Ng, Siow Woon; Hromadko, Ludek; Bures, Filip; Macak, Jan M. (Applied Materials Today, 2019)
Atomic layer deposition (ALD) represents a unique deposition technique that allows to coat uniformly various high aspect ratio (HAR) porous nanostructures, in addition to its traditional role to coat flat substrates (e.g. Si wafers). Self-organized anodic TiO2 nanotube (TNT) layers belong among the most investigated inorganic nanostructures. They possess highly functional materials with promising application potential across many technological fields. Herein, we review the utilization of ALD for the functionalization of anodic TNT layers by secondary materials to advance their physicochemical and photoelectrochemical properties. First, the application of ALD for functionalization of porous aluminium oxide, which represent fundamental HAR nanostructure, is briefly introduced. Then the main experimental parameters governing the uniformity and the conformality of ALD coating within HAR nanostructures are discussed. Finally, the review focuses on the use of ALD to deposit secondary materials into TNT layers for various purposes — the introduction of pioneering studies is followed by particular examples of ALD based functionalizations of coated TNT layers for optimized visible-light absorption, charge separation and passivation, (photo)catalysis, stability, gas sensing, and energy storage.
CRIS-Team Scopus Importer:2022-11-02
Keywords: Aspect ratio; Atomic layer deposition; Coatings; Functionalization; TiO